Pengaruh Game Terhadap Perkembangan Psikologi Anak - Nursidik; Akhmad Zaenul Ibad (PT FORMOSA CENDEKIA GLOBAL, 2022)
The nation's generation now lies in children who later grow up to become personal leaders. A leader who is able to lead himself is the most important factor. The thing that needs to be considered is character education that must be instilled from an early age. Education in the family which will be the foundation of character in behaving and behaving in society. However, with the development of media and technology, it becomes a challenge in character education. Many parents give their children the freedom they can by buying cellphones to play gametes from an early age. They reasoned that this action would be safer and easier to monitor the activities of the baby. But they have not thought about how the game affects the development that arises from the habit of playing games. Many negative impacts that will arise include: it will be difficult to socialize, slow in motor development, and significant behavioral changes. So it is very important the role of parents to supervise, control and pay attention to all children's activities.